Lower maternal emotional availability is related to increased attention toward fearful faces during infancy - Eskola, Eeva (Netherlands, 2025)
It has been suggested that infants’ age-typical attention biases for faces and facial expressions have an inherent connection with the parent–infant interaction. However, only a few previous studies have addressed this topic. To investigate the association between maternal caregiving behaviors and an infant’s attention for emotional faces, 149 mother–infant dyads were assessed when the infants were 8 months. Caregiving behaviors were observed during free-play interactions and coded using the Emotional Availability Scales. The composite score of four parental dimensions, that are sensitivity, structuring, non-intrusiveness, and non-hostility, was used in the analyses. Attention disengagement from faces was measured using eye tracking and face-distractor paradigm with neutral, happy, and fearful faces and scrambled-face control pictures as stimuli. The main finding was that lower maternal emotional availability was related to an infant’s higher attention to fearful faces (p = .042), when infant sex and maternal age, education, and concurrent depressive and anxiety symptoms were controlled. This finding indicates that low maternal emotional availability may sensitize infants’ emotion processing system for the signals of fear at least during this specific age around 8 months. The significance of the increased attention toward fearful faces during infancy is an important topic for future research.